A method for preparing S-type ZnO / Co3O4 heterojunctions and its application
Patent Information
- Application Number
- CN202610971203.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-30
AI Technical Summary
但是,CoO热力学稳定性较差,导致异质结组成和界面结构发生变化,从而影响材料性能的稳定性和重复性
(1)本发明制备的ZnO-CoO和ZnO- Co3O4的样品中均存在紧密结合的界面,能够大幅降低界面接触电阻,加速电子或空穴迁移,有效抑制载流子复合,提升材料整体电学与光电响应性能;且能够引入大量的界面活性位点,提高材料的反应活性,通过界面耦合实现性能互补,克服单一材料缺陷,改善材料的结构稳定性与循环使用性能;
Smart Images

Figure CN123021776A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional material preparation, specifically relating to a method for preparing an S-type ZnO / Co3O4 heterojunction and its application. Background Technology
[0002] ZnO is a typical wide-bandgap semiconductor (Eg≈3.2 eV) with advantages such as high electron mobility, good chemical stability, environmental friendliness, and low cost, and is widely used in photocatalytic degradation of pollutants, photocatalytic water splitting for hydrogen production, and CO2 reduction. Especially in photocatalytic reactions, ZnO possesses a suitable band structure and excellent charge transport capabilities, enabling the effective generation of photogenerated electron-hole pairs. However, the recombination rate of photogenerated carriers inside and on the surface of ZnO is relatively fast, and it is also prone to photocorrosion under illumination, severely limiting further improvements in its photocatalytic performance. Therefore, constructing heterostructures to improve the visible light response and carrier separation efficiency of ZnO has become an important research direction.
[0003] The preparation of ZnO and Co metal oxide heterojunctions is considered an effective method to improve the photocatalytic performance of ZnO. CoO is a p-type transition metal oxide. When ZnO and CoO are combined, due to the difference in their Fermi level and band structure, a pn heterojunction interface can be formed. A built-in electric field is generated at the interface, which promotes the directional migration and separation of photogenerated electrons and holes and inhibits carrier recombination. However, CoO has poor thermodynamic stability, which leads to changes in the heterojunction composition and interface structure, thus affecting the stability and reproducibility of material performance. Secondly, currently used methods are difficult to precisely control the ZnO-CoO interface, which easily leads to problems such as particle agglomeration, insufficient interface contact, and defect enrichment, which in turn form carrier recombination centers and reduce photocatalytic efficiency. Summary of the Invention
[0004] To address the problems existing in the prior art, the present invention provides a method for preparing S-type ZnO / Co3O4 heterojunctions.
[0005] Another objective of this invention is to provide the application of the above-mentioned S-type ZnO / Co3O4 heterojunction in photocatalytic energy conversion.
[0006] The technical solution adopted by the present invention to achieve the above objectives is as follows: This invention provides a method for preparing a ZnO / Co3O4S-type heterojunction, comprising the following steps: (1) Synthesis of ZnO nanodiscs First, zinc acetate dihydrate is added to methanol to obtain a zinc acetate solution; sodium hydroxide is added to water to obtain a sodium hydroxide solution; under vigorous stirring, the methanol solution of zinc acetate dihydrate is added to the sodium hydroxide aqueous solution, mixed evenly, and the reaction is carried out; after the reaction is completed, the mixture is centrifuged, washed, and dried to obtain zinc oxide powder. (2) Synthesis of ZnO / Co(OH)2 heterojunction ZnO powder was dissolved in a mixed solution; then Co(NO3)2·6H2O was added to the solution; then polyvinylpyrrolidone (PVP) was added, and the mixture was stirred for a period of time. NaOH aqueous solution was slowly added, and the mixture was stirred until homogeneous. The resulting suspension was heated to react; after cooling, the precipitate was centrifuged and washed to obtain ZnO / Co(OH)2. (3) Annealing yields ZnO / CoO heterojunction ZnO / Co(OH)2 was used as a calcination precursor and then annealed to obtain a ZnO / CoO heterojunction. (4) Annealing yields ZnO / Co3O4 heterojunction Using ZnO / CoO heterojunction as a calcination precursor, annealing was performed to obtain ZnO / Co3O4 heterojunction.
[0007] Preferably, in step (1), the mass ratio of zinc acetate dihydrate to sodium hydroxide is 1-1.2:0.2; the reaction is carried out in an oil bath at 60-65°C for 6 hours.
[0008] Preferably, in step (2), the mass ratio of ZnO powder to Co(NO3)2·6H2O is 0.067:0.24-0.96; the mixed solution is composed of deionized water and ethanol in a volume ratio of 1:1; the mass ratio of ZnO powder, polyvinylpyrrolidone and NaOH is 0.067:0.2:0.08-0.32; and the stirring time is 30-35 min.
[0009] Preferably, in step (2), the reaction is carried out by heating at 120-125°C for 10 hours.
[0010] Preferably, in step (3), the calcination is performed by annealing at 370 °C for 2 h in a nitrogen atmosphere with a flow rate of 50 mL / min.
[0011] Preferably, the annealing in step (4) is annealing at 350 °C for 5 min in an air atmosphere.
[0012] The present invention also provides an S-type ZnO / Co3O4 heterojunction prepared by the above preparation method.
[0013] Another objective of this invention is to provide the application of the above-mentioned S-type ZnO / Co3O4 heterojunction in photocatalytic energy conversion.
[0014] The ZnO-Co3O4 heterojunction prepared in this invention combines the excellent electron transport capability of ZnO with the good visible light absorption characteristics of Co3O4. After ZnO and Co3O4 come into contact, a stable pn heterojunction can be formed, generating a built-in electric field at the interface, effectively promoting the spatial separation of photogenerated electrons and holes and suppressing carrier recombination. Simultaneously, the narrow band gap of Co3O4 can broaden the system's photoresponse range and improve solar energy utilization efficiency, while its abundant Co... 2+ / Co 3+ Redox active sites enhance surface reaction kinetics. The ZnO / Co3O4 heterojunction prepared in this invention exhibits superior photocatalytic activity, stability, and recyclability compared to the ZnO / CoO heterojunction, showing broad application prospects in photocatalytic degradation of pollutants, photocatalytic water splitting for hydrogen production, and photoelectrochemical conversion.
[0015] The beneficial effects of this invention are as follows: (1) The ZnO-CoO and ZnO-Co3O4 samples prepared by this invention have tightly bound interfaces, which can significantly reduce the interfacial contact resistance, accelerate electron or hole migration, effectively suppress carrier recombination, and improve the overall electrical and photoelectric response performance of the material; and can introduce a large number of interfacial active sites to improve the reactivity of the material, achieve complementary performance through interfacial coupling, overcome the defects of single materials, and improve the structural stability and recycling performance of the material. (2) The heterojunction prepared by the present invention can form an S-type heterojunction with ZnO-Co3O4, which drives the carriers to migrate in a specific direction along a specific path. Electrons flow to Co3O4 to reduce CO2, while holes remain on ZnO to undergo oxidation reaction. This spatially separates the reactive sites, improves the charge transport rate, reduces energy loss during the transport process and inhibits photogenerated carrier recombination, while retaining a strong redox potential. (3) The preparation method provided by the present invention is simple, highly controllable, and capable of large-scale preparation. Attached Figure Description
[0016] Figure 1 The XRD patterns of the samples prepared in Example 1 are shown; (a) XRD patterns of ZnO-CoO and (b) XRD patterns of ZnO-Co3O4. Figure 2The figures show the characterization results of the samples prepared in Example 1; where: a, c) SEM images of ZnO / CoO and ZnO / Co3O4; b, d) top-view elemental distribution diagrams of ZnO / CoO and ZnO / Co3O4 nanoparticles; e, h) low-magnification bright-field TEM images of ZnO / CoO and ZnO / Co3O4, with the corresponding atomic structure models in the lower half; f, i) Fast Fourier Transform (FFT) analysis results of ZnO orientation along the [2-1-10] zone axis in ZnO / CoO and ZnO / Co3O4; g, j) high-resolution transmission electron microscopy (HRTEM) images showing the heterostructure interface of ZnO / CoO and ZnO / Co3O4. Figure 3 To show the band structure positions for experimental results; (ac) UV-Vis diffuse reflectance spectra of ZnO, CoO and Co3O4; (df) Mott-Schottky curves of ZnO, CoO and Co3O4; Figure 4 This is a schematic diagram of the band structure; Figure 5 (a, b) Photocatalytic CO2 reduction performance of ZnO / CoO and ZnO / Co3O4 samples; (c) Comparison of photocatalytic CO2 reduction performance of ZnO / Co3O4 sample with other heterojunction systems. Detailed Implementation
[0017] The technical solution of the present invention will be further explained and described below through specific embodiments.
[0018] Example 1 (1) Synthesis of ZnO nanodiscs First, weigh 1.097 g of zinc acetate dihydrate and add it to methanol to obtain a zinc acetate solution. Then, weigh 0.2 g of sodium hydroxide and add it to 50 mL of water to obtain a sodium hydroxide solution. Under vigorous stirring (ultrasonication), add the methanol solution of zinc acetate dihydrate to the sodium hydroxide aqueous solution, at which point the suspension turns white. Finally, place the above solution in a blue-capped bottle and incubate in an oil bath at 60 ℃ for 6 h. After naturally cooling to room temperature, collect the white zinc oxide powder by centrifugation, wash it with deionized water and anhydrous ethanol, and dry it overnight in a vacuum oven at 60 ℃. (2) Synthesis of ZnO / Co(OH)2 heterojunction ZnO / Co(OH)₂ heterojunctions with different Co(OH)₂ particle loadings were synthesized via a solvothermal method. First, 0.067 g of ZnO powder was dissolved in a mixed solution of 10 mL deionized water and 10 mL ethanol. Then, different masses of Co(NO₃)₂·6H₂O (0.24 g, 0.48 g, and 0.96 g) were added to the solution. Next, 0.2 g of polyvinylpyrrolidone (PVP) was added as a surfactant, and the mixture was stirred for 30 min. Then, 50 mL of an aqueous solution containing different masses of NaOH (0.08 g, 0.16 g, and 0.32 g) was slowly added, causing the solution color to change from light red to dark blue. Stirring continued for another 30 min. Finally, the resulting suspension was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 120 °C for 10 hours. After cooling, the precipitate was centrifuged and washed several times with ethanol and deionized water, and labeled as ZnO / Co(OH)2-N, where N represents the relative molar ratio of Zn to Co in the composite material.
[0019] (3) Annealing yields ZnO / CoO heterojunction ZnO / Co(OH)2 heterojunctions with different cobalt loadings were used as calcination precursors and annealed at 370 °C for 2 h in a tube furnace under a nitrogen atmosphere (flow rate 50 mL / min) to obtain a series of ZnO / CoO heterojunctions with different cobalt oxide loadings, labeled as ZnO / CoO-1, ZnO / CoO-2 and ZnO / CoO-4, respectively.
[0020] (4) Annealing yields ZnO / Co3O4 heterojunction Using ZnO / CoO heterojunctions with different cobalt loadings as calcination precursors, a series of ZnO / Co3O4 heterojunctions with different cobalt oxide loadings were obtained by annealing in an air atmosphere in a muffle furnace at 350℃ for 5 min, and labeled as ZnO / Co3O4-1, ZnO / Co3O4-2 and ZnO / Co3O4-4, respectively.
[0021] The XRD patterns of ZnO-CoO and ZnO-Co3O4 prepared in Example 1 are as follows: Figure 1 As shown in the figure, the XRD pattern confirms the successful synthesis of ZnO-CoO and ZnO-Co3O4 heterojunctions in Example 1. The XRD patterns are in high agreement with the standard diffraction peaks, confirming the successful construction of ZnO / CoO and ZnO / Co3O4 heterojunctions. ZnO corresponds to a wurtzite structure (JCPDS: 36-1451), CoO corresponds to a rock salt structure (JCPDS: 48-1719), and Co3O4 corresponds to a spinel structure (JCPDS: 42-1467). Figure 1 ).
[0022] The morphology of ZnO / CoO and ZnO / Co3O4 photocatalysts was characterized using scanning electron microscopy (SEM). Figure 2 As shown in a and c, CoO and Co3O4 nanoparticles are loaded onto the surface of ZnO nanodisks, with Co3O4 nanoparticles exhibiting a higher loading density and more uniform distribution. Energy-dispersive X-ray spectroscopy (EDX) elemental mapping further confirms its loading density and dispersion state. Figure 2 (b, d) indicates that the ZnO / CoO and ZnO / Co3O4 heterojunctions have been successfully constructed. Figure 2 As shown in e and h, low-magnification bright-field TEM images obtained along the [2-1-10] zone axis of ZnO show that CoO and Co3O4 nanoparticles are anchored on the (0001) crystal plane of ZnO, which is consistent with the SEM observation results. High-resolution transmission electron microscopy (HRTEM) images ( Figure 2 g and j) further revealed the atomic structure of the heterostructure interface. HRTEM images of the ZnO / CoO heterostructure interface showed that the (111) crystal plane of CoO was parallel to the (0001) crystal plane of the ZnO nanodisc. Similarly, the ZnO / Co3O4 heterostructure interface exhibited a clear orientation relationship: (111)Co3O4 / / (0001) ZnO and [1-10]Co3O4 / / [01-10]ZnO. These results confirm the formation of semi-coherent interfaces at the CoO / ZnO and Co3O4 / ZnO phase boundaries, and that tightly bonded interfaces exist in both the ZnO-CoO and ZnO-Co3O4 samples.
[0023] The band structure experimental results of ZnO / Co3O4-2 and ZnO / CoO-2 prepared in Example 1 are as follows: Figure 3 As shown, the light absorption capacity of the powder sample was determined using a UV-Vis-NIR spectrophotometer (Varian Cary 500 Scan). When the sample is irradiated with a light source, the interaction between the sample and the light produces two emission phenomena: crystal plane reflection and diffuse reflection. The catalyst powder sample has a small crystallite size, primarily producing diffuse reflection; therefore, its light absorption capacity can be measured using a spectrophotometer.
[0024] Specific testing method: Barium sulfate solid powder was used as the reference sample, and the scanning range was 250-800 nm. The diffuse reflectance of the sample was obtained experimentally, and then the diffuse reflectance of the material was converted into absorbance F(R) using the Kubelka-Munk equation, thus obtaining the UV-Vis DRS or ABS spectrum. The absorbance wavelength was used as the abscissa, and the absorbance of the material as the ordinate; the intersection of the linear portion of the spectrum and the abscissa is the band gap of the material. Sample preparation method: The solid powder sample was ground and added to a quartz sample stage, compacted and fixed with a glass cover, and placed in the instrument for testing after checking for any sample detachment.
[0025] The photoelectrochemical properties of the materials were tested using an electrochemical workstation (Bio-Logic VSP-300). Testing method: A standard three-electrode system was used, with Ag / AgCl and Pt electrodes serving as the reference and counter electrodes, respectively. The sample was drop-coated onto FTO as the working electrode, and Na₂SO₄ solution (0.2 M) was used as the electrolyte. Sample preparation method: 5 mg of solid powder sample was ultrasonically dispersed in 1 mL of DMF solution to obtain the sample solution. Then, a clean FTO sample was selected, and a 0.5 × 0.5 cm blank area was isolated on the FTO using transparent tape. 10 μL of the sample solution was pipetted onto the blank area of the FTO. After air drying, another 10 μL of solution was added, and after air drying again, the tape was removed. All areas except the sample were insulated with epoxy resin and then air-dried for later use. Mott-Schottky test: Set the frequency to 1.5-0.5 kHz, the amplitude to 25 mV, and the voltage to -1.0-0.6 V, and measure the Mott-Schottky curve.
[0026] The band gaps and energy level positions of ZnO, CoO, and Co3O4 were determined using UV-Vis DRS and Mott-Schottky measurements. Based on these band parameters, the charge transport behavior at the ZnO / Co3O4 heterostructure interface was predicted. Compared to ZnO / Co3O4, the ZnO / CoO heterostructure exhibits a smaller work function difference, resulting in a weaker built-in electric field (IEF). This makes it difficult for photogenerated electrons in the ZnO conduction band (CB) and photogenerated holes in the CoO valence band (VB) to recombine effectively at the interface. Furthermore, due to the nested (Type-I) band arrangement, the IEF-induced band bending allows photogenerated electrons in the ZnO conduction band to migrate directly across the heterostructure interface into CoO. Figure 4a). This process leads to carrier recombination within the CoO phase, significantly weakening photocatalytic performance. In contrast, the ZnO / Co3O4 heterostructure exhibits a larger work function difference and a stronger built-in electric field. Its S-scheme heterostructure suppresses the direct transport of conduction band photogenerated electrons. Driven by the built-in electric field, photogenerated electrons from ZnO and photogenerated holes from Co3O4 undergo efficient recombination at the interface ( Figure 4 b). This mechanism effectively retains electrons with strong reducing power in the Co3O4 conduction band for CO2 reduction reaction, thereby significantly improving photocatalytic efficiency.
[0027] In the absence of photosensitizers, co-catalysts, and sacrificial agents, this invention further investigated the photocatalytic CO2 reduction performance of the catalyst under visible light irradiation. For example... Figure 5 As shown in 5a and 5b, the ZnO / Co3O4 heterojunction exhibits the best photocatalytic activity, with peak evolution rates of 528, 94, and 42.67 μmol g⁻¹ h⁻¹ for CH₄, C₂H₄, and C₂H₆, respectively. The electron selectivity for CH₄ reaches a significant level of 70.9%. Compared with other materials disclosed in the prior art, the activity of ZnO / Co3O₄⁻² is at least about 2 times higher than that of other compounds. ZnO / Co3O₄⁻² possesses excellent photocatalytic CO₂ reduction activity (…). Figure 5 c).
Claims
1. A method for preparing a ZnO / Co3O4S-type heterojunction, characterized in that, Includes the following steps: (1) Synthesis of ZnO nanodisks First, zinc acetate dihydrate is added to methanol to obtain a zinc acetate solution; sodium hydroxide is added to water to obtain a sodium hydroxide solution; under vigorous stirring, the methanol solution of zinc acetate dihydrate is added to the sodium hydroxide aqueous solution, mixed evenly, and the reaction is carried out; after the reaction is completed, the mixture is centrifuged, washed, and dried to obtain zinc oxide powder. (2) Synthesis of ZnO / Co(OH)2 heterojunction ZnO powder was dissolved in a mixed solution; then Co(NO3)2·6H2O was added to the solution; then polyvinylpyrrolidone (PVP) was added, and the mixture was stirred for a period of time. NaOH aqueous solution was slowly added, and the mixture was stirred until homogeneous. The resulting suspension was then heated to react. After cooling, the precipitate was centrifuged and washed to obtain ZnO / Co(OH)2; (3) Annealing yields ZnO / CoO heterojunction ZnO / Co(OH)2 was used as a calcination precursor and then annealed to obtain a ZnO / CoO heterojunction. (4) Annealing yields ZnO / Co3O4 heterojunction Using ZnO / CoO heterojunction as a calcination precursor, annealing was performed to obtain ZnO / Co3O4 heterojunction.
2. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of zinc acetate dihydrate to sodium hydroxide is 1-1.2:0.2; the reaction is carried out in an oil bath at 60-65℃ for 6 hours.
3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the mass ratio of ZnO powder to Co(NO3)2·6H2O is 0.067:0.24-0.96; the mixed solution is composed of deionized water and ethanol in a volume ratio of 1:1; the mass ratio of ZnO powder, polyvinylpyrrolidone and NaOH is 0.067:0.2:0.08-0.32; and the stirring time is 30-35 min.
4. The preparation method according to claim 1 or 3, characterized in that, In step (2), the reaction is carried out by heating at 120-125°C for 10 hours.
5. The preparation method according to claim 1, characterized in that, In step (3), the calcination is performed by annealing at 370 °C for 2 h in a nitrogen atmosphere with a flow rate of 50 mL / min.
6. The preparation method according to claim 1 or 5, characterized in that, The annealing in step (4) is annealing at 350 °C for 5 min in an air atmosphere.
7. A ZnO / Co3O4S-type heterojunction prepared by the preparation method according to any one of claims 1-6.
8. The application of the ZnO / Co3O4S-type heterojunction as described in claim 7 in photocatalytic energy conversion.
